Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007615.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for prevention of neonatal hyperglycemia in very low birth weight infants

Abstract: Glucose infusion rate: There is insufficient evidence from trials comparing lower with higher glucose infusion rates to inform clinical practice. Large randomized trials are needed, powered on clinical outcomes including death, major morbidities and adverse neurodevelopment.Insulin infusion: The evidence reviewed does not support the routine use of insulin infusions to prevent hyperglycemia in VLBW neonates. Further randomized trials of insulin infusion may be justified. They should enrol extremely low birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…9 Hyperglycaemia: Hyperglycaemia (>8.3 mmol/L) is not uncommon in ELBW infants. 36 If blood glucose >10 mmol/L (moderate hyperglycaemia), 37,38 further management to control hyperglycaemia should be considered including reducing the glucose infusion rate (e.g. changing over to 7.5% Dextrose PN).…”
Section: Updated Consensus Formulationsmentioning
confidence: 99%
“…9 Hyperglycaemia: Hyperglycaemia (>8.3 mmol/L) is not uncommon in ELBW infants. 36 If blood glucose >10 mmol/L (moderate hyperglycaemia), 37,38 further management to control hyperglycaemia should be considered including reducing the glucose infusion rate (e.g. changing over to 7.5% Dextrose PN).…”
Section: Updated Consensus Formulationsmentioning
confidence: 99%
“…Hyperglycaemia: Hyperglycaemia (>8.3 mmol/L) is not uncommon in ELBW infants. 36 If blood glucose >10 mmol/L (moderate hyperglycaemia), 37,38 further management to control hyperglycaemia should be considered including reducing the glucose infusion rate (e.g. changing over to 7.5%…”
Section: Biochemical Monitoring On Pnmentioning
confidence: 99%
“…Elevated neonatal blood glucose concentration has been linked to adverse outcomes including death [36,37], intraventricular haemorrhage [36], late onset bacterial infection [38], fungal infection [39,40], retinopathy of prematurity [41-43] and necrotizing enterocolitis [38]. Attempts to maintain glucose intake using insulin have yielded variable results [44,45]. For prevention of hyperglycaemia, a systematic review found two small trials which compared lower versus higher glucose infusion rates [45].…”
Section: Standardised Pn Versus Individualized Pn Formulationsmentioning
confidence: 99%
“…Attempts to maintain glucose intake using insulin have yielded variable results [44,45]. For prevention of hyperglycaemia, a systematic review found two small trials which compared lower versus higher glucose infusion rates [45]. These trials provided some evidence that a lower glucose infusion rate reduced mean blood glucose concentrations and the risk of hyperglycaemia, but had insufficient power to test for significant effects on death or major morbidities [16,46].…”
Section: Standardised Pn Versus Individualized Pn Formulationsmentioning
confidence: 99%